THU0216 PERIPHERAL PROTEIN BIOMARKER CHANGES FOLLOWING SELECTIVE INHIBITION OF JANUS KINASE 1 (JAK1) BY FILGOTINIB IN METHOTREXATE NAÏVE ADULTS WITH MODERATELY-TO-SEVERELY ACTIVE RHEUMATOID ARTHRITIS (FINCH3). (13th June 2020) - Taylor, P. C.; Mirza, A. M.; Downie, B.; Liu, J.; Hawtin, R. E.; Elboudwarej, E.
Abstract : Background: Filgotinib (FIL), an oral selective JAK1 inhibitor, has shown efficacy and safety in multiple phase 3 studies in adults with moderately-to-severely active rheumatoid arthritis (RA), including those who are naïve to methotrexate (MTX) therapy (FINCH3; NCT02886728 ). Objectives: A longitudinal study of protein biomarkers related to JAK signaling 1, bone biology 2, immune cell migration 2, and inflammation 2 was conducted in FINCH3 pts to identify disease relevant biomarkers that are altered by FIL vs MTX. Methods: MTX-naive RA pts enrolled in FINCH3 received a stable dose of MTX (MTX mono), FIL200mg monotherapy (FIL200mg mono) or one of two doses of FIL once daily with MTX (FIL100mg+MTX, FIL200mg+MTX). Up to 27 disease relevant biomarkers were evaluated. Baseline (BL) correlation between biomarkers and clinical response measures were analyzed by Spearman Rank. Multiscale bootstrap resampling was used to evaluate significant intra-cluster biomarker membership. Mean changes in biomarker levels from BL to wks 4, 12 and 24 were compared between arms using MTX-adjusted estimates from a linear mixed effects model, adjusted for age, sex, race and BL biomarker level. A false discovery rate of 5% was applied for all analyses. Results: At BL, distinct clusters (CL) of biomarkers differentiated by JAK signaling were identified. The strongest intra-group correlations were in biomarkers upstream of JAK2 signaling (CL1; Rho range 0.88–0.98) and cytokines associated with JAK1 signaling (CL2; Rho range 0.72–0.77). Within MTX-naïve RA pts, there were significant BL correlations between 15 biomarkers and clinical measures. The strongest associations observed were between DAS28CRP and IL6, CXCL10, TNFRI, YKL-40, and CXCL13 (Rho >0.3). Relative to MTX mono, 23 biomarkers exhibited significant early responses to treatment (any arm, wk 4). The strongest treatment effect observed at wk 4 was a reduction by FIL+MTX (regardless of dose) and FIL200mg mono for CXCL13 (FIL100mg+MTX: -28.2%; FIL200mg+MTX: -40%; FIL200mg: -34%). This reduction was sustained in each arm through 24 wks, with the greatest reduction by FIL200mg+MTX (-37.8%). Dose differences were observed relative to FIL100mg+MTX, where FIL200mg+MTX led to an early (wk 4) and significantly greater reduction of 9 biomarkers. There was a significant dose difference as a delayed response (wk 24) with a greater reduction by FIL200mg+MTX for 8 biomarkers. FIL200mg mono produced a greater effect on 18 biomarkers vs MTX mono, remaining significant through wk 24. The greatest effect in FIL200mg mono were reductions by wk 24 in CTX1 (-29.1%), CXCL13 (-33.2%), and IL6 (-29.5%), all of which were biomarkers associated with DAS28CRP at BL. Effects observed at any time point were largely similar between FIL200mg as a mono or in combination with MTX. Four biomarkers were uniquely different between FIL200mg mono and FIL200mg+MTX arms by wk 24: greater increase of MMP7 and decrease of GMCSF in FIL200mg+MTX; greater decrease of TRACP5B and ICAM1 in FIL200mg alone. Conclusion: Treatment through 24 weeks with FIL200mg (mono or with MTX) reduced many of the disease-relevant biomarkers tested; markers related to JAK signaling 1, bone biology 2, inflammation 2, and immune cell migration 2 in the MTX-naïve RA setting. Changes were significantly reduced relative to MTX mono at wk 4, supporting the rapid onset of FIL clinical efficacy. The current study identified significant reductions of RA-associated disease markers that were unique to FIL mono, supporting the FIL mechanisms of action in the treatment of RA. References: [1]Majoros A, et al. Front Immunol. 2017;8:29 [2]Brennan F, and McInnes I. J Clin Invest. 2008;118:3537-45 Acknowledgments: This study was funded by Gilead Sciences, Inc. Editorial support was provided by Fishawack Communications Inc and funded by Gilead Sciences, Inc. Disclosure of Interests: Peter C. Taylor Grant/research support from: Celgene, Eli Lilly and Company, Galapagos, and Gilead, Consultant of: AbbVie, Biogen, Eli Lilly and Company, Fresenius, Galapagos, Gilead, GlaxoSmithKline, Janssen, Nordic Pharma, Pfizer Roche, and UCB, Amer M. Mirza Shareholder of: Gilead Sciences Inc., Employee of: Gilead Sciences Inc., Bryan Downie Shareholder of: Gilead Sciences Inc., Employee of: Gilead Sciences Inc., Jinfeng Liu Shareholder of: Gilead Sciences Inc., Roche, Employee of: Gilead Sciences Inc., Rachael E. Hawtin Shareholder of: Gilead Sciences Inc., Employee of: Gilead Sciences Inc., Emon Elboudwarej Shareholder of: Gilead Sciences Inc., Employee of: Gilead Sciences Inc.